PERANAN KEGIATAN EKSTRAKURIKULER BELADIRI TAEKWONDO TERHADAP HASIL BELAJAR PJOK SISWA-SISWI KELAS VIII SMP MANDIRI KOTA PALEMBANG - periyadi, Al (Jurnal Dosen Universitas PGRI Palembang)
Abstrack:Taekwondo is a modern martial sport rooted in traditional Korean martial art, taekwondo has many advantages, not only teaches about physical asfek, such as fighting skills, but also emphasizes the teaching aspect of mental discipline. The background of this research, that began the erosion of discipline, responsibility, manners reduced sense of brotherhood is being eroded by the progress of time. In extracurricular activities, this study aims to find out how big the role of extracurricular activities taekwondo martial on learning outcomes pjok (sports physical education and health). Based on the results of data analysis showed that the role of extracurricular activities taekwondo martial arts on learning outcomes pjok students of class VIII JSS Mandiri Palembang city categorized either 80.46%. Based on the study above it can be concluded that the taekwondo martial extracurricular activities are very big role on learning outcomes pjok.Keyword: Taekwondo, Sport Educaution, Student,